Dunia tanpa sempadan : cabaran terhadap pembangunan modal insan berdaya saing / Azman Ibrahim - Ibrahim, Azman (Faculty of Information Management, 2009)
The term globalisation has been used to describe the high mobility in capital, product and services from the one nation to other pans of the world. In order to face the challenges of globalisation, the Malaysian government has taken up measures to equip the local human capital with the essential knowledge. Local Human Capital is the new super/van J of locally breed human capital that would lead the nation into globalisation and liberalisation. Education, training and reengineering have been identified as the core of breeding the global human capital.